Характеристика городского населения согласно данным Всеобщей национальной переписи 2002 года - Стык, Ю. (Социология: теория, методы, маркетинг, 2005)
It is the first introductory of Polish urban population emerging from the National Census 2002. It gives an overview of demographical structure dynamics of Polish urban population in comparison to the rural one. The analysis covers such areas as the respondents’ marital status, educational structure, migrations and spatial mobility, family and children, professional activity, unemployment, sources of income and living conditions. The collected data show the progressing differentiation of economic situation and social status of urban population. Unemployment causes significant worsening of living conditions.